2023
DOI: 10.1007/s11250-023-03620-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulant potential of Moringa Oleifera leaves alcoholic extract versus Oregano Essential Oil (OEO) against cyclophosphamide-induced immunosuppression in broilers chicks

Abstract: The current study was conducted to evaluate the immunoenhancement effect of Moringa oleifera leaves alcoholic extract (MOLE) versus Oregano essential oil (OEO) against cyclophosphamide induced immunosuppression in broilers chicks. A total of a three hundred one-day-old chicks were assigned randomly into three main dietary groups, control, MOLE, and OEO for 14 days. After 14 days the three main experimental groups were subdivided into six groups, control, cyclophosphamide, MOLE, MOLE and Cyclophosphamide, OEO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Stankiewicz et al, reported that oxidative stress and elevated reactive oxygen species (ROS) could play an important role in cyclophosphamide-induced kidney damage 3 . Furthermore, prior studies demonstrated that cyclophosphamide could inhibit the activities of antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT) 4,5 . Other theories related to nephrotoxicity due to cyclophosphamide were imbalance of the oxidants-antioxidants system, increase of the inflammatory cytokines, and apoptosis 6 , although there is no consensus that, to prevent the toxicity due to cyclophosphamide, a potent antioxidant agent could be useful.…”
Section: Introductionmentioning
confidence: 99%
“…Stankiewicz et al, reported that oxidative stress and elevated reactive oxygen species (ROS) could play an important role in cyclophosphamide-induced kidney damage 3 . Furthermore, prior studies demonstrated that cyclophosphamide could inhibit the activities of antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT) 4,5 . Other theories related to nephrotoxicity due to cyclophosphamide were imbalance of the oxidants-antioxidants system, increase of the inflammatory cytokines, and apoptosis 6 , although there is no consensus that, to prevent the toxicity due to cyclophosphamide, a potent antioxidant agent could be useful.…”
Section: Introductionmentioning
confidence: 99%